Implementation Of Early Marriage Age Restrictions Policy (Case Study Of Religious Affairs Office, Paguyaman District, Boalemo Regency) - Abdullah, Sri Ainun; Tahir, Arifin; Nani, Yacob Noho (Universitas Negeri Gorontalo, 2025)
This study aims to describe (1) Implementation of Early Marriage AgeRestriction Policy (Case Study of Religious Affairs Office, Paguyaman District,Boalemo Regency) (2) Inhibiting factors in the implementation of early marriagepolicy (Case Study of Religious Affairs Office, Paguyaman District, BoalemoRegency). The approach in this study uses a qualitative approach with adescriptive research type. Data collection in the study using observation,interview, and documentation techniques. The results of this study are that (1)Implementation of Early Marriage Age Restriction Policy in Paguyaman District,Boalemo Regency consisting of communication, resources, disposition andbureaucratic structure. Of the four aspects, it is not yet effective enough inimplementation. (2) the determining factors for the success of theimplementation of the Early Marriage Age Restriction policy in PaguyamanDistrict, Boalemo Regency, seen from environmental, social, and cultural aspects,are not yet good enough. There still needs to be a more holistic and sensitiveapproach to local conditions.